Genetic dissimilarity between castor bean cultivars using RAPD markers - Machado, Edna Lôbo; Silva, Simone Alves; Santos, Agenildo de Sousa; Bastos, Leila Andrade; Pestana, Camila Nogueira; Santos, Keylla Souza dos; Ferreira, Cláudia Fortes; Diamantino, Maria Selma Alves Silva (Pesquisa Agropecuaria Brasileira, 2013)
The objective of this work was to identify genetically different cultivars of castor bean (Ricinus communis) using RAPD markers. A total of 58 RAPD primers were used to genotype 15 cultivars. The genetic dissimilarity between cultivars was calculated by Jaccard’s index, using the unweighted pair‑group method with arithmetic mean (UPGMA). Five hundred and fifty‑two fragments were identified, of which 311 were polymorphic (56.3%). The cultivars were clustered in five groups, evidence that there is genetic difference among them. RAPD markers are efficient in the study of genetic dissimilarity in castor bean.